7-2(3x-1)+16=8x+11

Simple and best practice solution for 7-2(3x-1)+16=8x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-2(3x-1)+16=8x+11 equation:


Simplifying
7 + -2(3x + -1) + 16 = 8x + 11

Reorder the terms:
7 + -2(-1 + 3x) + 16 = 8x + 11
7 + (-1 * -2 + 3x * -2) + 16 = 8x + 11
7 + (2 + -6x) + 16 = 8x + 11

Reorder the terms:
7 + 2 + 16 + -6x = 8x + 11

Combine like terms: 7 + 2 = 9
9 + 16 + -6x = 8x + 11

Combine like terms: 9 + 16 = 25
25 + -6x = 8x + 11

Reorder the terms:
25 + -6x = 11 + 8x

Solving
25 + -6x = 11 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
25 + -6x + -8x = 11 + 8x + -8x

Combine like terms: -6x + -8x = -14x
25 + -14x = 11 + 8x + -8x

Combine like terms: 8x + -8x = 0
25 + -14x = 11 + 0
25 + -14x = 11

Add '-25' to each side of the equation.
25 + -25 + -14x = 11 + -25

Combine like terms: 25 + -25 = 0
0 + -14x = 11 + -25
-14x = 11 + -25

Combine like terms: 11 + -25 = -14
-14x = -14

Divide each side by '-14'.
x = 1

Simplifying
x = 1

See similar equations:

| (x^2)^2/x^2x | | 1/T=1/7t=1/9t=8 | | 3*(2*x+3)=-2(5x-6) | | (x2)^2/x^2x | | 25n^2+15n+2=0 | | 2n=40n+3 | | 16=x^2+2x | | x+(0.14)=4500 | | y=4x^2+4x-8 | | 5x(2-7x)= | | 3x-5=6(x-3) | | 2(x+4)-(5-2x)=5 | | 7n(-3+5n)+2= | | 5x^2-35x-10=0 | | 4-5x=9+8x | | 80-y=20 | | 3/8=rt2/3 | | 8(2x+3)=4 | | -4(5x-8)= | | 12=7x-72 | | 50-5(2x+4)=20x-100 | | .5t+.1=3-t | | -18z-3=-3z-2 | | 1/f=1/2+1/4 | | 1/2•1/3 | | 1+2(y+4)= | | -1d=4d | | y/8-2=6 | | 2x-3y=125 | | x^2+8xy+16y^3=0 | | 12/5÷60 | | -18=-7w+12 |

Equations solver categories